PENINGKATAN DAYA PADA PEMBANGKIT LISTRIK MIKROHIDRO (PLTMh) DI DAERAH IMOGIRI BANTUL JOGJAKARTA - Suyanto, Muhammad (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
In rural areas there is generally a major irrigation canal that serves to irrigate the fields and also has the potential to be used as power plants. Developments Wukirsari Imogiri Bantul area, an agricultural region and its inhabitants have a side job as grate the coconut and make various handicrafts for souvenirs that use raw materials from a particular timber. Development of today's technology provides a variety of environmental impacts, both positive and negative, in the presence of micro hydropower plant in one of the villages in the area Imogiri will certainly add a positive impact for local communities. In the presence of micro-hydro, if night can be used as a means of public street lighting so that security and a sense of anxiety at night reduced incomes and to increase trade group be established to process the materials of wood and iron to take advantage of wood-working equipment that require electricity results from the existing micro-hydro power, yet still very limited relative kapisitasnya. Side activity that utilizes peratan carpentry can not be fulfilled using electricity from existing plants.Therefore we need an increased effort on Micro Hydro Power (MHP) is still very limited relative power. So in this study, is expected to obtain an increase in power can be realized with both and can obtain results in line with expectations.